2014
DOI: 10.3389/fped.2014.00100
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure, Heart Rate, and CNS Stimulant Medication Use in Children with and without ADHD: Analysis of NHANES Data

Abstract: It is estimated that 2–3% of children in the US have hypertension (HTN) and 8% of children ages 4–17 carry the diagnosis of attention-deficit hyperactivity disorder (ADHD). The prevalence of HTN and cardiovascular (CV) risk factors in children with ADHD on CNS stimulant treatment (stimulants) compared to no treatment and compared to their healthy counterparts is not well described. Using National Health and Nutrition Survey data, we examined demographic, blood pressure (BP) and CV risk factors of 4,907 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 21 publications
(24 reference statements)
1
7
0
Order By: Relevance
“…Despite the ubiquitous use of stimulant drugs to treat ADHD, there is concern for associated adverse events. Several recent studies [9,10] have suggested an increased risk of experiencing a later cardiovascular event when taking stimulants in childhood and children with ADHD on stimulants have significantly higher heart rates than children with ADHD not taking stimulants or children without ADHD [9]. There is also evidence that long-term stimulant use may impact the growth trajectories of children.…”
Section: Stimulantsmentioning
confidence: 99%
“…Despite the ubiquitous use of stimulant drugs to treat ADHD, there is concern for associated adverse events. Several recent studies [9,10] have suggested an increased risk of experiencing a later cardiovascular event when taking stimulants in childhood and children with ADHD on stimulants have significantly higher heart rates than children with ADHD not taking stimulants or children without ADHD [9]. There is also evidence that long-term stimulant use may impact the growth trajectories of children.…”
Section: Stimulantsmentioning
confidence: 99%
“…As noted before, both isomers nonselectively release monoamines into the synaptic cleft. While d-AMP has a fourfold greater impact on dopamine than l-AMP, this needs to be put in context as a relative assessment because both isomers can increase striatal dopamine by greater than 5000% of the baseline value (Heal et al 2013). In a similar vein, l-AMP has a comparable or greater impact on norepinephrine when compared to d-AMP, but both isomers have a very potent effect (Heal et al 2013;Markowitz and Patrick 2017).…”
Section: Enantiomersmentioning
confidence: 99%
“…While d-AMP has a fourfold greater impact on dopamine than l-AMP, this needs to be put in context as a relative assessment because both isomers can increase striatal dopamine by greater than 5000% of the baseline value (Heal et al 2013). In a similar vein, l-AMP has a comparable or greater impact on norepinephrine when compared to d-AMP, but both isomers have a very potent effect (Heal et al 2013;Markowitz and Patrick 2017). This must be interpreted in the context of nonracemic mixtures of AMP isomers in which d-AMP predominates (e.g., mixed AMP salt formulations) (Markowitz and Patrick 2017).…”
Section: Enantiomersmentioning
confidence: 99%
See 1 more Smart Citation
“…When children with ADHD are treated with stimulants, they often show an increase of their usually low BP concurrently with symptom improvement [ 51 , 52 , 53 , 54 ]. This clinical observation and additional findings from diurnal heart rate, cortisol level and sleep stages suggest a dysregulation of the autonomic nervous system in children with ADHD and leads to the subcortical (low) arousal hypothesis.…”
Section: Discussionmentioning
confidence: 99%